Vladimir Prelog i Zavod za organsku kemiju - Jakopčić, K. (Kemija u Industriji, 2007)
The Department of organic chemistry was founded on October 1st, 1922 as part of the Chemical Engineering Department of the High Technical School in Zagreb. The first-appointed professor of organic chemistry was Ivan Marek, formerly the professor at the School of Trade in Zagreb. The High Technical School with all its departments was soon (1926/27) incorporated into the University of Zagreb and became the nucleus of the Technical Faculty. The management of the faculty was fully aware of the necessity to engage the best scientists in the field as faculty professors. As far as organic chemistry was concerned, there was no better choice in the mid 1930's, than to invite young but already recognized organic chemist Dr. Vladimir Prelog to join the staff and to succeed professor Marek, who retired in 1935. Dr. Prelog did not hesitate to accept the invitation and was eager to continue his scientific work in an academic laboratory in Zagreb. At the time of the invitation, Dr. Prelog was engaged in a small laboratory synthesizing special samples of rare chemicals to be sold through the chemical store "Dřiza" in Prague. There he was provided the modest opportunity to carry on his own research, and together with Rudolf Lukeš and Emil Votoček, published a number of papers concerning organic synthesis and chemistry of natural products. Elected in Zagreb for the lectureship of the assistant professor in organic chemistry, Prelog started teaching as early as in the summer semester of 1934/35. The ingenious and bright lecturing of young professor Prelog inspired his students, and many of them were attracted to organic chemistry. On the other hand, the working conditions in the disposable laboratory of the Organic Chemistry Department were too modest to accept a number of students. The budget was so small that it only covered tuition, while there was no research fund at the faculty. Luckily, Dr. Prelog did not hesitate to accept an offer for scientific co-operation from the small but prosperous pharmaceutical company "Kaštel" in Zagreb. On behalf of the agreement, Prelog and his department obtained funds to fit up the laboratory and to start very prosperous research in the synthesis and studies of pharmaceutically interesting compounds. With his assistants, students and other collaborators, Prelog started research of cinchona bark alkaloids, preferentially oriented to the synthesis of quinine. For example, Prelog's method of double intramolecular alkylation to synthetize the quinuclidine moiety of quinine was patented by "Kaštel". With R. Seiwerth he developed the first useful synthesis of adamantane. Prelog's group started research in the field of sulphonamides and commercial success of "Streptazole" stimulated the development of the research laboratories within "Kaštel". The collaboration in the research continued in fields of other chemotherapeutics, analeptics, spasmolitics, barbiturates etc. Within the period 1935-1941, Prelog published 48 scientific papers and 8 patents. In less than seven years, his results enormously influenced the entire organic chemistry in Zagreb till nowadays. Under the confused and uncertain circumstances caused by the beginning of World War II, Prelog left Zagreb in 1941 and continued his extraordinary scientific career at the ETH in Zürich.During the war (1942-1945) the tuition and the Department were run by Dr. Rativoj Seiwerth, former collaborator and first assistant to V. Prelog. In almost unbelievable conditions, the young assistant, then assistant professor (since January 1943), R. Seiwerth fully succeeded in continuing most activities founded by Professor Prelog. After the war (1945), R. Seiwerth was forced to resign. Nevertheless, soon after R. Seiwerth continued his research work, firstly in the Institute for Industrial Research in Zagreb (1946-1952), and later in the Research Institute of "Pliva" in Zagreb. He retired in 1980.In post-war conditions (1945/46), the activity of the Technical Faculty and its Organic Chemistry Department was restored. The tuition and leading of the Department were offered to Dr. Viktor Hahn, former student and Prelog's collaborator since 1936. The influence of Professor V. Hahn on the development of the Technical Faculty and the Department of Organic Chemistry in the period 1945-1970 (V. Hahn ceased on May 17, 1970) was enormous. Thanks to the well-established research and tuition in the Department, his former students and colleagues have successfully continued the work until today.